1978
DOI: 10.1055/s-0028-1097386
|View full text |Cite
|
Sign up to set email alerts
|

A Phytochemical Study of Calligonum comosum L. Henry

Abstract: From the herb of Calligonum comosum (Polygonaceae) the flavonoids Kaempferol, Quercetin, Quercetin-3-0-@-D-glucoside (Isoquercitrin) and Kaempferol-3-0-@-D-glucuronide, procyanidines and the carotenoids Violaxanthin and Neoxanthin have been isolated and identified mainly by chemical and spectroscopic methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1990
1990
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…EI-mass spectra showed [M] + at m/z 462, suggesting the molecular formula C 21 H 18 O 12 , and the main fragment at 286, suggesting the aglycone C 15 H 10 O 6 The data suggested that compound 7 is kaempferol-3-O-glucuronide which has been previously isolated from the herb of Calligonum comosum L. (El-Sayyad and Wagner, 1978).…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…EI-mass spectra showed [M] + at m/z 462, suggesting the molecular formula C 21 H 18 O 12 , and the main fragment at 286, suggesting the aglycone C 15 H 10 O 6 The data suggested that compound 7 is kaempferol-3-O-glucuronide which has been previously isolated from the herb of Calligonum comosum L. (El-Sayyad and Wagner, 1978).…”
Section: Resultsmentioning
confidence: 78%
“…220Ð222 ∞C, soluble in methanol, slightly soluble in ethyl acetate and insoluble in chloroform, diethyl ether and benzene. Compound 6 was identified as isoquercitrin (quercetin-3-Oglucopyranoside) which has been previously isolated from the herb of Calligonum comosum L. (El-Sayyad and Wagner, 1978).…”
Section: Resultsmentioning
confidence: 99%
“…Antimicrobial activity for different plant parts was reported (Riadh et al 2011;Alkhalifah 2013). Previous phytochemical studies on C. polygonoides reported the isolation of kaempferol, quercetin, (+)-catechin, dehydrodicatechin A, kaempferol-3-O-rhamnopyranoside, quercitrin, isoquercitrin, kaempferol-3-Oglucuronide, quercetin-3-O-glucuronide, pro-cyanidines, b-sitosterol-3-O-glucoside, violaxanthin and neoxanthin carotenoids (El-Sayyad & Wagner 1978;Badria et al 2007). …”
Section: Introductionmentioning
confidence: 99%
“…Features have been extracted by screening the detected nodes at various retention times per minute, with a minimum intensity of 6,000 counts, and aligned with previously detected compounds considering adducts ([M + H] + , and [M−H] − ). The tentatively identified compounds are Catechin, ( Markham, 1982 ), Dehydrodicatechin A, ( Markham, 1982 ), Quercetin-3-O-Glucuronide, ( Markham, 1982 ), Tamgermanetin, ( Jayaprakasha et al, 2006 ), Methyl Gallate, ( Jayaprakasha et al, 2006 ), 5-(3-Hydroxyphenyl)Pentanoic Acid, ( Jayaprakasha et al, 2006 ), and Kaempferol 3-O-Glucoside-7-O-Rhamnoside, ( el Sayyad and Wagner, 1978 ), Means m / z implies measured m / z .
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, peak F showed m / z value at retention time (30.365–30.560) was correlated with the parent compound 5-(3-Hydroxyphenyl) Pentanoic Acid, with m / z [M + H] + 195.1090 Da and a molecular formula of [C 11 H 14 O 3 ] + , [M + H] + m / z 194.23 in positive ion mode, and [M−H] − with m / z 193.73 Da in negative mode, indicating that the compound has a molecular weight of 194.23 g mol −1 (27). In addition, peak G exhibited m / z value at retention time (33.165–33.215) was correlated with the parent compound Kaempferol 3-O-Glucoside-7-O-Rhamnoside, with m / z [M + H] + 595.4009 Da and a molecular formula of [C 11 H 14 O 3 ] + , [M + H] + m / z 594.50 in positive ion mode, and [M−H] − with m / z 593.83 Da in negative mode, indicating that the compound has a molecular weight of 594.36 g mol −1 ( el Sayyad and Wagner, 1978 ).…”
Section: Discussionmentioning
confidence: 99%